Identity and Social Status in Language Used: An Explorative Study on Guess Who’s Coming To Dinner Tonight - Rianita, Dian; Martin, Laily (Andalas International Journal of Socio-Humanities, 2020)
Language usage has functions to express ideas, and simultaneously can promote the speakers’ identities and social status. Identity markers such as race, gender, class and ethnicity have important roles to choose language used. This paper explores the correspondence between language, identity and social status as exposed in a classic film entitled “Guess who’s coming to dinner tonight” released in 1967. The utterance of the characters in the movie will be analyzed in order to illustrate the vital role of language as a part of promoting the speaker's identity and social status. The study also emphasizes language choice, such as specific vocabulary, and share attitude when discussing a sensitive topic. As a finding, there are significant points that language use inevitably promotes the speakers' social identity due to their academic backgrounds and beliefs.